2023
DOI: 10.1089/ham.2018.0052
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Genetic Variants of the Peroxisome Proliferator-Activated Receptor-Alpha Gene to High-Altitude Hypoxia Adaptation in Sherpa Highlanders

Abstract: The contribution of genetic variants of the gene encoding peroxisome proliferator-activated receptor-alpha gene (PPARA) to high-altitude hypoxia adaptation in Sherpa highlanders. High Alt Med Biol. 16:000-000, 2018.-Sherpa highlanders, who play invaluable roles in the exploration of Mount Everest, have exceptional tolerance to hypobaric hypoxia. Sherpa people are well known to possess the traits determined by genetic background for high-altitude adaptation. The metabolic adaptation mechanism is one of the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The physiological and particular respiratory adaptation of the Tibetans has also been studied, 51,52 since they live in one of the most extreme high‐altitude conditions (an average of approximately 4000 m 53 ). Genetic variations in Tibetans have produced an increase in blood lactate levels and, particularly for Sherpas, it has been identified that PPARA gene expression (PPAR‐alpha is a transcription factor) is involved in regulating the expression of some genes involved in metabolic processes 54 . However, genetic mechanisms that cause these metabolic adaptations remain unidentified 55 .…”
Section: Resultsmentioning
confidence: 99%
“…The physiological and particular respiratory adaptation of the Tibetans has also been studied, 51,52 since they live in one of the most extreme high‐altitude conditions (an average of approximately 4000 m 53 ). Genetic variations in Tibetans have produced an increase in blood lactate levels and, particularly for Sherpas, it has been identified that PPARA gene expression (PPAR‐alpha is a transcription factor) is involved in regulating the expression of some genes involved in metabolic processes 54 . However, genetic mechanisms that cause these metabolic adaptations remain unidentified 55 .…”
Section: Resultsmentioning
confidence: 99%
“…PPARα, a member of nuclear receptor transcription factors family, is highly expressed in the heart, liver, kidney, and skeletal muscle where energy metabolism is quite active, regulating the lipid metabolism and gluconeogenesis, specifically the fatty acid beta-oxidation in mitochondrial and peroxisomal [41]. Hypoxia condition enhances the procedure of anaerobic glycolysis and lactic acid accumulation in venous blood that is regulated by PPARα to enhance the utilization ratio of oxygen and keep the brain supplied with sufficient ATPs [42]. Decreased fatty acid oxidation in skeletal muscle is observed in Sherpa highlanders and Tibetans because fatty acid oxidation needs more oxygen when producing the same amount of ATPs [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia condition enhances the procedure of anaerobic glycolysis and lactic acid accumulation in venous blood that is regulated by PPARα to enhance the utilization ratio of oxygen and keep the brain supplied with sufficient ATPs [42]. Decreased fatty acid oxidation in skeletal muscle is observed in Sherpa highlanders and Tibetans because fatty acid oxidation needs more oxygen when producing the same amount of ATPs [42,43]. A putatively advantageous PPARA haplotype exhibited a significantly positive relationship with decreased expression or activity of PPARα and increased serum free fatty acid in Tibetans, demonstrating that PPARA is associated with hypoxia metabolic adaptation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Sherpa carriers of the positively selected PPARA alleles switch to more efficient fuels such as glucose and display decreased muscular fatty acid oxidation (Horscroft et al, 2017). Most of the PPARA SNPs reported to be under selection appear to be non-coding variants (Kinota et al, 2018). It is unclear if these variants directly affect transcriptional regulation or are linked with functional variants in other genes or nearby inter-genic regions.…”
Section: Signatures Of Altitude-related Genetic Selection In the Sherpamentioning
confidence: 99%